The Importance of Financial Literacy: How to Educate Yourself About Money and Make Sound Financial Decisions - Suharlina, Suharlina (Accounting Studies and Tax Journal (COUNT), 2024)
Financial literacy plays an important role in individual financial decision making at various stages of life. The aim of this research is to systematically reflect on the literature to explore the influence of financial literacy on individual financial decision making at various stages of life. The research method uses a systematic approach in searching and analyzing relevant articles from reputable international databases. The results of the discussion show that financial literacy has a significant impact on financial decision making, with a higher level of literacy endangering better financial decisions. The implication of this research is the importance of increasing financial literacy at various levels of society, both through formal education and other financial education programs.